P-OGC35 Does Adjuvant Chemotherapy Provide Additional Survival Benefit AfterNeoadjuvant Chemotherapy or Chemoradiotherapy and Esophagectomy forEsophageal Adenocarcinoma?. (16th December 2021) - Kamarajah, Sivesh; Markar, Sheraz; Phillips, Alexander; Kunene, Victoria; Fackrell, David; Salti, George; Dahdaleh, Fadi; Griffiths, Ewen
Abstract: Background: The evidence assessing the additional benefits of adjuvant chemotherapy (AC) following neoadjuvant therapy (NAT; i.e. chemotherapy or chemoradiotherapy) and esophagectomy for esophageal adenocarcinoma (EAC) are limited. This study aimed to determine whether AC improves long-term survival in patients receiving NAT and esophagectomy. Methods: Patients receiving esophagectomy for EAC following NAT from 2004 - 2016 were identified from the National Cancer Data Base (NCDB). Patients with survival < 6 months were excluded to account for immortality bias. Propensity score matching (PSM) and Cox regression was performed to account for selection bias and analyze impact of AC on overall survival. Results: Overall 12, 972 (91%) did not receive AC and 1, 255 (9%) received AC. After PSM there were 2, 485 who received AC and 1, 254 who did not. After matching, AC was associated with improved survival (median: 38.5 vs 32.3 months, p < 0.001), which remained after multivariable adjustment (HR: 0.78, CI 95% : 0.71 - 0.87, p < 0.001). On multivariable interaction analyses, this benefit persisted in subgroup analysis for nodal status: N0 (HR: 0.85, CI 95% : 0.69 - 0.96, p = 0.039), N1 (HR: 0.66, CI 95% : 0.56 - 0.78, p < 0.001), N2/3 (HR: 0.80, CI 95% : 0.66 - 0.97, p = 0.024) and margin status: R0 (HR: 0.77, CI 95% : 0.69 - 0.86, p < 0.001), R1 (HR: 0.60, CI 95% : 0.43 - 0.85, p = 0.004). Further, patients with stable disease following NAT (HR: 0.60, CI 95% : 0.59 - 0.80, p < 0.001) or downstaged (HR: 0.80, CI 95% : 0.68 - 0.95, p = 0.009) disease had significant survival benefit after AC, but not patients with upstaged disease. Conclusions: AC following NAT and esophagectomy is associated with improved survival, even in node-negative and margin-negative disease. NAT response appears crucial in identifying patients who will benefit maximally from AC, and thus future research must be focused on identifying tumors that respond to chemotherapy to maximize this prognostic benefit.